Detection and characterization of citrus viroids in Malaysia using reverse transcription- polymerase chain reaction - Murugan, Taneswari (2016)
Citrus belongs to Rutaceae family and sub-family Aurantoidea originated in Southeast Asia and it is a major fruit crop throughout world. Viroids have been reported in citrus species causing Citrus Exocortis disease, Citrus Cachexia disease, Citrus Leaf Bending disease, Citrus Bark Cracking disease and Citrus Dwarfing disease. These diseases cause a reduction in yield and quality of citrus production. Yet, there is no study or information on citrus viroids in Malaysia. The purpose of this study is to identify and characterize citrus viroid in Malaysia. A total of 33 citrus samples showing leaf bending, petiole necrosis, vein yellowing, and stunting symptoms were collected from Muar, Johor and Kajang, Selangor. RNA was extracted using TELSP buffer and was amplified by Reverse Transcription- Polymerase Chain Reaction (RT-PCR) using six different sets of citrus viroid specific primers. The RT-PCR products fractionated using 2% agarose gel and the viroid positives samples produced expected size of amplicon (200-300 bp). A total of 2 out of 16 samples from Muar and 2 out of 17 samples from Kajang were positive by RT-PCR. Positive RT-PCR products were purified and sent for sequencing. Blast analysis for sequences of all the four PCR positive samples showed high sequence similarity (95 to 99%) with Citrus bent leaf viroid (CBLVd) isolate lot3/3-1, complete genome (Genbank: KM214210.1) and the nucleotide size ranged from 192 to 218 nt. The viroid was found in C. aurantifolia, C. hystrix and C.sinensis which showed virus and viroid like symptoms and this is the first report of CBLVd in Malaysia.